Studi Kasus Tentang Pengolahan Tanah Dengan Bajak Singkal Dan Rotary Terhadap Sifat Fisik Tanah Pada Budidaya Tanaman Padi Sawah - Ade Purbayuda Manik; I Wayan Tika; I Gusti Ngurah Apriadi Aviantara (Program Studi Teknik Pertanian dan Biosistem, Fakultas Teknologi Pertanian, Universitas Udayana, Badung, Bali, Indonesia, 2017)
This study was conducted to compare some soil physical properties in two different rotary. The variables measured in this study are: texture, soil porosity, density, volume weight, and productivity. The results showed that the treatment using ordinary plow and rotary plow texture hisher the same texture class silty clay loam. The treatment using the rotary plow has a porosity namely than rotary plow. The width of each sampling area is 20- 40 are. The mass volume on ordinary plow was higher than the rotary plow. The productivity of ordinary plow treatment has higher than rotary plow. The productivity of the ordinary plow treatment were 6,9 ton/ha, 7,8 ton/ha and 8,8 ton/ha for red rice, cigeulis variety and qluti nous rice respectively. The productivity of the rotary plow treatment were 6,6, 6 and 6,8 ton/ha for red rice, cigeulis variety and qluti nous rice.